(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The influence of food on eggs’ hatching of Plodia interpunctella (Hbn.) was valued; 24 substrates were tested. 100 eggs were placed on a first layer of product about 2-3mm thick and afterwards they were covered with a second layer of equal thickness. 4 replications were carried out for every product. In absence of food, the eggs show the highest average values for hatching (95±0.4). The lowest average values of hatching were observed on finely ground pine seeds (6±0.7) and on finely ground almonds (11.8±1.4), while those higher than 90 are observed for castor sugar, powdered cinnamon, dried yeast and powdered garlic.